2021
DOI: 10.1080/10717544.2021.1960922
|View full text |Cite
|
Sign up to set email alerts
|

In silico identification and experimental validation of cellular uptake by a new cell penetrating peptide P1 derived from MARCKS

Abstract: Viral vectors for vaccine delivery are challenged by recently reported safety issues like immunogenicity and risk for cancer development, and thus there is a growing need for the development of non-viral vectors. Cell penetrating peptides (CPPs) are non-viral vectors that can enter plasma membranes efficiently and deliver a broad range of cargoes. Our bioinformatic prediction and wet-lab validation data suggested that peptide P1 derived from MARCKS protein phosphorylation site domain is a new potential CPP can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 53 publications
(83 reference statements)
1
11
0
Order By: Relevance
“…FITC-labeled KKP1 in the cell has the strongest fluorescence intensity during the initial 1 and 2 h of treatment and gradually decreased after 4, 8, 16, and 24 h (Figures D,E and S3). Our previous publications suggest that a penetration enhancer can significantly enhance the penetration efficiency of the well-known different CPPs including hPP3, hPP10, , MT23, Scp01-b, Dot1l, P2, and P1 . We wanted to address whether the penetration efficiency of KKP can further be enhanced.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…FITC-labeled KKP1 in the cell has the strongest fluorescence intensity during the initial 1 and 2 h of treatment and gradually decreased after 4, 8, 16, and 24 h (Figures D,E and S3). Our previous publications suggest that a penetration enhancer can significantly enhance the penetration efficiency of the well-known different CPPs including hPP3, hPP10, , MT23, Scp01-b, Dot1l, P2, and P1 . We wanted to address whether the penetration efficiency of KKP can further be enhanced.…”
Section: Resultsmentioning
confidence: 64%
“…Thus, effective therapeutic strategies are still in urgent demand. We successfully developed a variety of delivery vectors of CPPs to deliver biotherapeutics into intracellular in vitro cultured cells and the in vivo mouse model. ,,, ,,, Thus, with our combined expertise, we attempted to develop a CPP-based PROTAC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our studies also suggested although 36 + GFP can significantly enter cells and tissues compared with GFP protein, the penetration efficiency of 36 + GFP is still limited. Following our previous studies (Ma et al., 2015 ; Wang et al., 2016a , 2016b , 2016c ; Zhou et al., 2017 ; Ding et al., 2019 ; Zhang et al., 2019 ; Chen et al., 2021 ; Guo et al., 2021 ), we conducted 5% DMSO treatment in cultured cells, and found that the efficiency of 36 + GFP mediated transduction itself and its mediated transfection were significantly increase thus these results are consistent with our previous published studies. These data indicated that penetration enhancer application is another alternative approach to enhance the penetration and relative delivery efficiency of peptide or supercharged proteins- based delivery vectors.…”
Section: Discussionmentioning
confidence: 77%
“…Nanoparticles. NPs are composed of particles dispersed below nanometers or solid particles with a size span of 10-1000 nm with biomimetic attributes [31,32]. Biomimetic attributes increase in combination with the high surfaceto-volume proportion.…”
Section: Nanocarriers As a Promising Instrument Formentioning
confidence: 99%